Nitrogen explosion pretreatment of lignocellulosic material for bioethanol production. Issue 12 (17th June 2016) - Tutt, Marti; Raud, Merlin; Kahr, Heike; Pointner, Manuel; Olt, Jüri; Kikas, Timo
ABSTRACT: A novel method for the pretreatment of lignocellulosic material is investigated in this work, using floodplain meadow hay as a feedstock for bioethanol production. Pressurized nitrogen (N2 ) pretreatment is combined with explosive decompression to achieve high glucose yields with simple technology and low energy input. Results show that N2 explosion yields hydrolysis efficiencies up to 71.8%. The highest hydrolysis efficiency was achieved at a temperature of 210°C with a cellulose to glucose conversion rate of 195.1 g kg −1 of biomass.